2013
DOI: 10.1097/iae.0b013e318261a6b5
|View full text |Cite
|
Sign up to set email alerts
|

Preretinal Partial Pressure of Oxygen Gradients Before and After Experimental Pars Plana Vitrectomy

Abstract: Preretinal PO2 gradients are not eliminated after pars plana vitrectomy. During BSS perfusion, vitreous cavity PO2 is very high. Interruption of BSS perfusion evokes progressive equilibration of vitreous cavity PO2 with concomitant progressive return of preretinal PO2 gradients to their previtrectomy patterns. This indicates that preretinal diffusion of oxygen is not altered after vitrectomy. The beneficial effect of vitrectomy in ischemic retinal diseases or macular edema may be related to other mechanisms, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 44 publications
(59 reference statements)
1
11
0
Order By: Relevance
“…The gelled vitreous is 99% water, so after vitrectomy, when the vitreous is 100% water, would not matter. Consistent with this, Petropolous et al (Petropoulos et al, 2013) convincingly showed experimentally that O 2 gradients do not change after vitrectomy. Arguments that it does change (Gisladottir et al, 2009; Stefansson and Loftsson, 2006) are based on considering the vitreous as a viscous fluid rather than a gel and are not valid (Barton et al, 2007).…”
Section: Oxygen and Diabetesmentioning
confidence: 60%
See 4 more Smart Citations
“…The gelled vitreous is 99% water, so after vitrectomy, when the vitreous is 100% water, would not matter. Consistent with this, Petropolous et al (Petropoulos et al, 2013) convincingly showed experimentally that O 2 gradients do not change after vitrectomy. Arguments that it does change (Gisladottir et al, 2009; Stefansson and Loftsson, 2006) are based on considering the vitreous as a viscous fluid rather than a gel and are not valid (Barton et al, 2007).…”
Section: Oxygen and Diabetesmentioning
confidence: 60%
“…However, the preretinal vitreous PO 2 is not always sufficient for understanding inner retinal PO 2 . Alder and Cringle (Alder and Cringle, 1985, 1990) and others (Buerk et al, 1993; Petropoulos et al, 2013) have shown that gradients of PO 2 extend for several hundred μm into the vitreous and they depend on the proximity to retinal vessels. PO 2 is higher at the retina near arterioles, and decreases with distance into the vitreous from the retina.…”
Section: Fundamentals Of O2 Supply To the Retinamentioning
confidence: 94%
See 3 more Smart Citations